Assessment of spatial changes in the duck harvest within the Central Flyway, 1997–2011 - Haugen, Matthew T.; Powell, Larkin A.; Vrtiska, Mark V. (Wildfowl, 2014)
Knowledge of the factors which influence the spatial distribution of duck harvest would be useful to managers when setting dates for the duck hunting seasons. HereÂ we used changes in mean latitude of harvest to represent changes in distribution ofÂ duck harvest during the hunting season within the Central Flyway from 1997â€“2011,Â derived from harvest data from the U.S. Fish and Wildlife Service Parts CollectionÂ Survey. A candidate set of models was developed to represent competing hypothesesÂ of corn availability, weather, water on the landscape, competition via populationÂ density, hunting pressure, and regulatory change to explain the variation in harvestÂ distribution of Mallard Anas platyrhynchos, dabbling ducks Anas sp., and diving ducksÂ Aythya sp. The model selection process revealed that hunting pressure, the amount ofÂ water on the landscape, and Mallard density best explained the distribution of MallardÂ harvest. Mallard harvest distributions tended to be further north during wet years ofÂ high Mallard densities and low hunting pressure, relative to dry years with highÂ Mallard densities and low hunting pressure. High hunting pressure shifted the spatialÂ distribution of Mallard harvest further south. Regulations had the largest influence onÂ both dabbling (non-Mallard) and diving duck harvest distribution. Dabbling duckÂ harvest distribution was further north under the 2002â€“2011 frameworks, relative toÂ the 1997â€“2001 frameworks. During the 2002â€“2011 frameworks, diving ducks wereÂ more likely to be harvested further south early in the season and further north later inÂ the season, relative to 1997â€“2001 frameworks. Trends in the distribution of harvestÂ should be informative for future harvest management decisions.